Psychological and social wellbeing associated with regional population change in Finland - Jokela, Markus; Laakasuo, Michael; Parikka, Suvi; Rotkirch, Anna; Hämäläinen, Hans (Wiley, 2025)
Regional depopulation is an increasingly common demographic issue in many countries, as population growth becomes concentrated in small number of urban centres. Depopulation has adverse effects on the region's socioeconomic development, and often leads to worse living circumstances, such as poor availability of services. Population growth, by contrast, has many socioeconomic benefits but may also introduce unwanted consequences, such as urban alienation. However, the associations of regional population change with inhabitants' psychological and social wellbeing have not been examined as extensively as the associations with socioeconomic outcomes. With a large survey dataset from Finland (n = 99,034 participants from 299 municipalities), we examined whether regional, municipality-level population decline and growth over the preceding 10 years were associated with psychological and social wellbeing of the inhabitants of the municipalities. We were specifically interested in whether growth and decline were both related to these outcomes, or whether the associations were more pronounced for either decline or growth. Overall negative population change was related to lower social wellbeing (e.g., lower social support) and that these associations were more pronounced for the adverse associations of population decline than for the beneficial associations of population growth (e.g., less frequent social contact and higher risk of loneliness). Population change was not associated with inhabitants' depressive symptoms. These findings suggest that regional population decline can be particularly relevant for worsening social wellbeing of the inhabitants.